Mewujudkan Kebun Bergizi di Desa Tou Barat - Ensu Ensu; Fadilatul Afidah; Zubaidah Zubaidah; Yeremias Bardi; Astuti Dewi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This study aims to improve food security and nutritional status in the Tou Barat Village community, Kota Baru District, Ende Regency, by utilizing their yards as nutrition gardens. The main problem faced by the community is low vegetable and fruit consumption due to limited land, nutritional knowledge, and access to nutritious food. The implementation method uses a participatory approach through education, training, and direct mentoring for villagers. The activity stages include counseling on the benefits of nutrition gardens, selecting superior seeds, land preparation, planting, and plant care using polybag, hydroponic, and vertical cultivation systems. The results showed a significant increase in community participation, with involvement reaching 240 families, a 300% increase compared to the previous program. This program successfully utilized unproductive land as a source of nutritious food that helps prevent stunting and strengthens family economic independence. In addition, the nutrition gardens serve as an educational medium that raises awareness of the importance of a healthy and environmentally friendly diet. Overall, this program has proven effective in promoting local food security, community empowerment, and the implementation of sustainable agricultural principles.